2020
DOI: 10.1016/j.jtocrr.2020.100024
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Surveillance Monitoring of Circulating Tumor DNA From Patients With SCLC Detects Disease Relapse and Predicts Death in Patients With Limited-Stage Disease

Abstract: Introduction: Most patients (70%) with limited-stage SCLC (LS-SCLC) who are treated with curative-intent therapy suffer disease relapse and cancer-related death. We evaluated circulating tumor DNA (ctDNA) as a predictor of disease relapse and death after definitive therapy in patients with LS-SCLC. Methods: In our previous work, we developed a plasmabased ctDNA assay to sequence 14 genes (TP53, RB1, BRAF, KIT, NOTCH1-4, PIK3CA, PTEN, FGFR1, MYC, MYCL1, and MYCN) that are frequently mutated in SCLC. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…In line with our results, it's well reported that cancer patients present higher cfDNA levels than healthy controls (46,47) but few studies have investigated the possible prognostic and predictive value of total cfDNA quantification in patients with SCLC. In contrast, the ctDNA, the tumor-derived fraction of this cfDNA, has been reported as a prognostic and predictive biomarker in several works (48)(49)(50)(51)(52). Almodovar et al reported that changes in the mutant allele frequencies on ctDNA were associated with response to treatment and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, it's well reported that cancer patients present higher cfDNA levels than healthy controls (46,47) but few studies have investigated the possible prognostic and predictive value of total cfDNA quantification in patients with SCLC. In contrast, the ctDNA, the tumor-derived fraction of this cfDNA, has been reported as a prognostic and predictive biomarker in several works (48)(49)(50)(51)(52). Almodovar et al reported that changes in the mutant allele frequencies on ctDNA were associated with response to treatment and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors observed a higher percentage of alterations in APC and AR in samples obtained at relapse. Recently, it has been hypothesized that the detection of ctDNA in patients with LS-SCLC after definitive therapy would predict disease relapse and death, after showing that residual ctDNA can be detected prior to radiographic relapse [ 76 ]. Overall, all of these studies demonstrate that cfDNA analyses constitute a powerful tool for SCLC diagnosis, therapy selection and monitoring that can be a key element to improve this tumor management in the close future.…”
Section: Liquid Biopsy As a Clinical Tool In Sclcmentioning
confidence: 99%
“…In line with our results, it's well reported that cancer patients present higher cfDNA levels than healthy controls (38,39) but few studies have investigated the possible prognostic and predictive value of total cfDNA quantification in patients with SCLC. In contrast, the ctDNA, the tumor-derived fraction of this cfDNA, has been reported as a prognostic and predictive biomarker in several works (40)(41)(42)(43)(44). Almodovar et al reported that changes in the mutant allele frequencies on ctDNA were associated with response to treatment and relapse.…”
Section: Discussionmentioning
confidence: 99%